Anti-inflammatory property of quercetin through downregulation of ICAM-1 and MMP-9 in TNF-α-activated retinal pigment epithelial cells. (April 2019) - Cheng, Shu-Chen; Wu, Yi-Hong; Huang, Wen-Chung; Pang, Jong-Hwei S.; Huang, Tse-Hung; Cheng, Ching-Yi
Graphical abstract: Highlights: TNF-α induces THP-1 adhesion via the expression of ICAM-1 or MMP-9 in ARPE-19 cells. Quercetin attenuates TNF-α-induced the expression of ICAM-1 and MMP-9. Quercetin inhibits TNF-α-activated MEK1/2–ERK1/2–c-Jun pathway in ARPE-19 cells. Quercetin attenuates TNF-α-induced NF-kB activation via the PKCδ– JNK1/2 pathway. Abstract: Quercetin is a flavonoid polyphenolic compound present in fruits and vegetables that has proven anti-inflammatory activity. The goal of the present investigation was to investigate the effects of quercetin on tumor necrosis factor-α (TNF-α)-induced inflammatory responses via the expression of ICAM-1 and MMP-9 in human retinal pigment epithelial cells (ARPE-19 cells). Real-time PCR, gelatin zymography, and Western blot analysis showed that TNF-α induced the expression of ICAM-1 and MMP-9 protein and mRNA in a time-dependent manner. These effects were attenuated by pretreatment of ARPE-19 cells with quercetin. Quercetin inhibited the TNF-α-induced phosphorylation of PKCδ, JNK1/2, ERK1/2. Quercetin, rottlerin, SP600125 and U0126 attenuated TNF-α-stimulated c-Jun phosphorylation and AP-1–Luc activity. Pretreatment with quercetin, rottlerin, SP600125, or Bay 11-7082 attenuated TNF-α-induced NF-κB (p65) phosphorylation, translocation and RelA/p65–Luc activity. TNF-α significantly increased MMP-9 promoter activity and THP-1 cell adherence, and these effects were attenuated by pretreatment with quercetin, rottlerin, SP600125, U0126, tanshinone IIA or Bay 11-7082. These results suggest that quercetin attenuates TNF-α-induced ICAM-1 and MMP-9 expression in ARPE-19 cells via the MEK1/2–ERK1/2 and PKCδ–JNK1/2–c-Jun or NF-κB pathways.